Skrining Fitokimia dan Profil Kromatografi Lapis Tipis (KLT) Tumbuhan Antimalaria Asal Indonesia: Phytochemical Screening and Thin Layer Chromatography Profile of Indonesia Plants - Muhammad Arifuddin; Mahfuzun Bone (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Phytochemical screening tests have been carried out to detect secondary metabolites in several plants, namely Brotowali stem (Tinospora crispa), Jambu Biji leaves (Psidium guajava), Manggis rind (Garcinia mangostana), Pare fruit (Momordica charantia), Pepaya leaves (Carica papaya), Pulai sari stem bark (Alstonia scholaris), Sirsak leaves (Annona muricata). The test results obtained the state that each sample of the plant contains secondary metabolites which have the potential as antimalarial compounds.